Analysis of Quizizz-assisted natural and social sciences (IPAS) learning in relation to learning-style preference categories of fifth-grade students at SD Inpres Perumnas Palu - Muslih Rifandani; Nasrullah Nasrullah; Muslim AR; Arif Firmansyah; Ryan Andhika Pratama (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2026)
This study explored Quizizz-assisted Natural and Social Sciences (IPAS) learning in relation to learning-style preference categories among fifth-grade students at SD Inpres Perumnas Palu. A qualitative descriptive design was used. Thirty students were invited to complete a learning-style questionnaire, and 28 responses were used to identify visual, auditory, and kinesthetic categories. One student from each category and the classroom teacher participated in classroom observations, semi-structured interviews, and documentation. Data were analyzed through data reduction, data display, and conclusion drawing. The visual-category participant was particularly engaged by images, colors, animations, and the leaderboard. The auditory-category participant described Quizizz as enjoyable but still relied on direct teacher explanations to understand new material. The kinesthetic-category participant was more active during the quiz activity and responded positively to competition, although teacher guidance remained important. At the class level, Quizizz supported an active formative-assessment atmosphere, but limited Chromebook availability and unstable internet connectivity constrained implementation. These findings are context-specific descriptions of participants’ preferences and experiences; they do not demonstrate that matching instruction to learning styles improves learning outcomes.